2004
DOI: 10.1111/j.1440-1673.2004.01273.x
|View full text |Cite
|
Sign up to set email alerts
|

Silent embolism in diagnostic cerebral angiography: Detection with diffusion‐weighted imaging

Abstract: Angiography has known and documented risks of neurological events. We prospectively studied 20 patients who underwent diagnostic cerebral angiographic examinations and diffusion-weighted MRI (DWI). Eighteen patients had DWI before and after their angiogram, whereas two patients had a DWI only after their angiogram (DWI was normal in both of these patients). No clinical neurological deficits were detected in any of our patients after angiography, but in three of 20 patients there was a new hyperintense signal a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
23
3
3

Year Published

2006
2006
2020
2020

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 38 publications
(31 citation statements)
references
References 12 publications
(13 reference statements)
2
23
3
3
Order By: Relevance
“…The annual rate of RCC diagnosis is increasing as a result of incidental detection by crosssectional abdominal imaging of patients with suspected abdominal disorders. Increased detection rates carry a favourable prognosis; however, mortality from RCC has not decreased [2][3][4].Diffusion-weighted imaging (DWI) is frequently used in cranial MRI studies and has shown potential for the characterisation of lesions such as acute cerebral infarctions, intracranial tumours, various infectious diseases and metabolic disorders [5][6][7][8]. The role of DWI is limited outside the central nervous system, owing to its inherent extreme sensitivity to motion, such as that related to respiration, peristalsis and artefacts, thus resulting in a high signal to noise ratio.…”
mentioning
confidence: 99%
“…The annual rate of RCC diagnosis is increasing as a result of incidental detection by crosssectional abdominal imaging of patients with suspected abdominal disorders. Increased detection rates carry a favourable prognosis; however, mortality from RCC has not decreased [2][3][4].Diffusion-weighted imaging (DWI) is frequently used in cranial MRI studies and has shown potential for the characterisation of lesions such as acute cerebral infarctions, intracranial tumours, various infectious diseases and metabolic disorders [5][6][7][8]. The role of DWI is limited outside the central nervous system, owing to its inherent extreme sensitivity to motion, such as that related to respiration, peristalsis and artefacts, thus resulting in a high signal to noise ratio.…”
mentioning
confidence: 99%
“…Previous reports have indicated that incidental embolism is not rare, and past history of vasculopathy, amount of contrast medium used, fluoroscopy time, use of additional catheters, procedures of the occlusion test, and performance of endovascular surgery for cerebrovascular disease are risk factors for embolism. 1,4,5,8,9,11,13,16,17,20,21) Angiography of the coronary arteries also carries a risk for cerebral embolism due to the duration of the procedure. 4,15) Diffusion-weighted MR imaging (DWI) allows for the most sensitive early detection of cerebral ischemia within minutes of onset.…”
Section: Introductionmentioning
confidence: 99%
“…Our thrombi, after days 1 and 3, however, were hypointense on DWI. This discrepancy could be explained by the fact that clinical manifestations of CVT are variable and do not coincide with radiological demonstration of venous thrombi [30].…”
Section: Experimental Venous Thrombi: Mri With Histopathological Corrmentioning
confidence: 93%